Gestational diabetes mellitus causes dyslipidemia in late trimester: mini review - S., Poonguzhalai; P., Kalyanikutty K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The incidence of gestational diabetes mellitus (GDM) is increasing rapidly worldwide. Many women with gestational diabetes mellitus are likely to have type 2 diabetes. With the extensive management protocol for GDM we are able to obtain a good glycaemic control but still excess morbidity prevails among GDM pregnancy compared to normal pregnancy. This may be due to the dysfunction of lipid metabolism. Changes in carbohydrate and lipid metabolism occur during pregnancy to ensure a continuous supply of nutrients to the growing fetus despite intermittent maternal food intake. Exaggerated reduction in insulin sensitivity in the peripheral tissues combined with peripheral adipose tissue lipolysis in GDM pregnancy than normal pregnancy results in increased maternal lipoprotein concentrations and elevated lipoprotein triglyceride content. An altered lipid profile on the maternal side would modulate the quantity and quality of lipids being transferred to the fetus. Hypertriacylglycerolemia in gestational diabetes mellitus has been related to a significant risk of having neonates that are large for gestational age and it is considered as a major cause of preeclampsia in the late gestational age. So, the recent researchers emphasize on targeting lipid metabolism in pregnant women with GDM to avoid the adverse outcomes of pregnancy.